Fungi That Produce Toxins in Salted Fish - Yuli Susanti; Ratih Dewi Dwiyanti (Tropical Health and Medical Research, 2019)
Salted fish are fish that are processed through a process of salting and drying. The contamination of fungi in salted fish can be caused by prolonged storage. Storage of salted fish that is too long can cause the growth of various fungi. One of the fungi that often grows in salted fish is the fungus of Aspergillus sp. Some species of the Aspergillus sp fungi can produce aflatoxin, one of which is Aspergillus flavus. This study aims to determine the contamination of toxin-producing fungi in salted fish in the traditional Banjarbaru market in Indonesia. The type of research used is descriptive survey. Samples were taken by purposive sampling taken from 5 salted fish sellers each taken 3 different types of salted fish so that the number of samples was 15. The results were obtained from 15 samples examined, 6 positive samples contaminated with Aspergillus flavus fungi, 8 positive samples contaminated with Aspergillus fungi niger, 5 positive samples contaminated with Monilia sitophila fungi, 6 positive samples contaminated with Rhizopus sp fungi, 6 positive samples contaminated with Penicillium sp fungi, and 1 positive sample contaminated with Mucor sp fungi. Based on the results of the study, samples of salted fish contaminated with Aspergillus sp fungi were 73% (11 samples) and no samples were contaminated with Fusarium sp.